Presença, escuta e compreensão integrativa: um olhar dialógico sobre a relação médico-paciente - Martucelli, Fátima Aparecida Gomes (2011)
The present study about the doctor-patient relationship aims to use the bibliographic review to present a historical overview on the behaviors of the doctor-patient relationship, the quality of hearing and presence in times of pain and suffering from the beginning of medicine to the current days. Study analysis prove advances in medical and technology fields do not replace the doctor-patient relationship. Such relationship is taken as a first and essential source to adhere to treatments, support to face the obstacles arising out of acute and chronic illnesses. We also discuss the Fritz Perls Gestalt-therapy approach, focusing on the theoretical scope of the individual relationship to its environment. The main concepts of the Gestalt-therapy are: contact, contact roles, contact limits, support and awareness, and they are part of men s relationship to his environment, favoring an integrative presence in the self and the world. We believe such approach may provide facilitating instruments to improve the quality of presence, hearing and integrating understanding of the doctor-patient relationship. Buber s Dialogic Relationship inserts the dialogue in the between and the alternation of the encounter. It indicates a therapeutic attitude based on Inclusion, Presence and Commitment to the dialogue, as well as the conditions required to have a high-quality encounter. Those are suggestions for a better clinical practice of the doctor-patient relationship